Langerhans Histiocytosis in a Child – Diagnosed by Oral Manifestations - Shruti Golai (Journal of Clinical and Diagnostic Research, 2015)
Langerhans Histiocytosis (LCH) is a rare reactive and proliferative disease of histiocytes with unknown etiology, characterized by excessive proliferation of histiocytes called Langerhans cells. It occurs mainly in children but occurrence in adults has also been reported. It manifests as punched out lesions in the skull, maxilla, mandible, sternum and other flat bones and causes rapid resorption of the alveolar bone leading to floating teeth appearance in the radiographs. This disease manifests initially in the oral cavity in most of the cases and can be diagnosed by careful clinical and radiological examination. Here, we present a case of LCH in a child which was diagnosed by a swelling in the mandibular region.